Metode Sosiodrama dalam Meningkatkan Kecerdasan Moral Anak - Latifah Nur Ahyani; Dhini Rama Dhania (Lembaga Penelitian Universitas Muria Kudus, 2011)
Children grow and develop in a life colored by the violation of others right, crime, compulsion, ignorance, unclearness between right and wrong, good and bad, allowed and not allowed behaviors. Building moral intelligence is very important to do in order that the childrens intuition is able to differentiate the right and the wrong. Thus, they can reject the bad influences from outside. One of the ways used to give moral value to the children is sociodrama.The research aims to know the sociodrama method in improving the moral intelligence of children. Subject of the research is the student of elementary school. The number of subject in the experiment and control groups is same that is 14 students.The research is design using model of The Untreated Control Group Design with Pretest and Posttest. The design uses two groups examined which consist of an experiment group and a control group. The measurement is conducted twice using moral intelligence measurement instrument, namely before it is given treatment (pre-test) and after it has been given treatment (post-test).The result of analysis using T-Test shows that there is a difference of moral intelligence achievement level of the children between those who receive moral value guidance through sociodrama method and those who do not receive moral value guidance through sociodrama method p = 0,009 (p less than 0,05). The result of analysis also shows that there is difference of moral intelligence achievement level of th children before receiving moral value guidance through sociodrama method and after they have receive the moral value guidance through sociodrama method p = 0,033 (p less than 0,05). The result of analysis shows the great contribution of sociodrama method towards the moral intelligence of children is 30,9%.